Late Ordovician (Sandbian–Hirnantian) marine gastropods from the Argentine Precordillera: their biogeographical significance in a middle to high latitudinal setting - Mariel Ferrari; Verónica Bertero; Marcelo G. Carrera (Acta Palaeontologica Polonica)
Gastropods from the Upper Ordovician of the Argentine Precordillera received less attention than other coeval marine invertebrates in this region. The present contribution supplies accurate taxonomic information recovering 10 gastropod genera which are represented by 10 species from the La Pola and Don Braulio formations (Sandbian and Hirnantian units, respectively) at the San Juan Province, Argentina: two species, namely Tetranota argentina sp. nov. and Clathrospira gondwanica sp. nov., are new to science. The gastropod association shows a remarkable diversity, and in contrast to other invertebrate groups reported in the Argentine Precordillera (e.g., trilobites, ostracodes, brachiopods, sponges, and bivalves) which had Gondwanan affinities during the Late Ordovician, the gastropod assemblage from the La Pola and Don Braulio formations had major palaeobiogeographical similarities with their Northern Hemisphere (Laurentia, Avalonia, and Baltica) counterparts. The occurrence of the genus Clathrospira suggests that it could have been the first precursor of the order Pleurotomariida in South America during the Sandbian–Hirnantian, and can help to shed light on the origin of this clade in the southernmost Gondwana continent as early as Palaeozoic times.